Pacjenci onkologiczni w środowisku pracy – reakcje i wsparcie ze strony współpracowników - Ulaniecka, Natalia (Kultura-Społeczeństwo-Edukacja, 2023)
The article discusses the challenges cancer patients face in the workplace, with a focus on the reactions and support they receive from their colleagues. The study involved indepth interviews with cancer patients, employers representatives, and trade union representative. Specific examples of support and negative reactions were discussed - during treatment and in return-to-work process (RTW) after absence. The article also provides quotes from the respondents to highlight the diverse experiences of cancer patients in the workplace. The study revealed knowledge deficits among colleagues regarding the specificities of cancer, particularly in relation to long-term side effects. It also highlighted the persistent stereotypes and fears associated with cancer. Therefore, there is a need for social education to increase awareness about cancer and its long-term consequences, better communication among colleagues, and constructive support for cancer patients in the workplace.